Primary fallopian tube carcinoma associated with ovulation induction; a case report. Issue 6 (1st October 2008) - Deliveliotou, A.; Hassiakos, D.; Fotiou, S.; Karvouni, E.; Creatsas, G.
Abstract : The potential relationship between ovulation induction and gynecological cancer has been raised recently. Primary fallopian tube carcinoma (PFTC) is an uncommon malignancy, not previously associated with fertility drugs use. We describe a case of a 38-year-old woman with primary infertility and a history of three ovulation inductions with gonadotropin-releasing hormone agonist and gonadotrophins, referred for treatment of bilateral ovarian cysts, which were discovered in the beginning of the last cycle. During laparotomy, bilateral adnexal masses were identified, presumed to be of ovarian origin, and total abdominal hysterectomy, bilateral salpingo-oophorectomy, infracolic omentectomy, and retroperitoneal lymph nodes sampling were performed. Histologic examination showed a primary right fallopian tube endometrioid adenocarcinoma and bilateral adnexal endometriosis. Surgery was followed by six cycles of combination chemotherapy using paclitaxel and carboplatin without significant complications. Although evidence of a direct causal link between ovarian stimulation and PFTC does not yet exist, this case highlights the importance for careful evaluation of all discovered adnexal masses in women undergoing ovulation induction treatment.